DETERMINAN YANG MEMPENGARUHI NIAT MAHASISWA MELAKUKAN TINDAKAN WHISTLEBLOWING (STUDI PADA MAHASISWA AKUNTANSI UNIVERSITAS BRAWIJAYA) - Astrid Dwi Nastiti (Jurnal Ilmiah Mahasiswa FEB, 2018)
This research aims at proving empirically the effect of attitude, subjective norm, perceivedbehavioral control, Machiavellian characteristic, and academic performance on the intention ofcommit whistleblowing. The object of the study is accounting student at the University ofBrawijaya. The data were collected through the survey method with questionnaires given to 60respondents who were determined by the proportionate stratified random sampling technique.The data were analyzed using multiple regression analysis. The result of the analysis showedthat attitude, subjective norm, perceived behavioral control, and Machiavellian characteristicinfluence the intent to commit whistleblowing. Meanwhile, academic performance does notaffect the intent.Keywords: theory of planned behavior, Machiavellian characteristic, whistleblowin